The Effect Of Total Asset Turnover Ratio, Company Size And Leverage On Stock Returns In Food And Beverage Companies Listed On The Indonesia Stock Exchange In The 2018-2021 Period - Putri Z, Andini; Aswin Akbar (SEAN Institute, 2024)
A stock return refers to the projected profit or rate of return that investors expect from their investment in a company. This research aims to evaluate the influence of leverage, company size, and total asset turnover on the stock returns of food and beverage companies listed on the Indonesia Stock Exchange between 2018 and 2021. Purposive sampling is the approach utilized in this study for sample selection; nine samples were chosen for this study. In this study, descriptive statistical methods were employed as the analytical approach. SPSS version 26 software is utilized for data processing, and the data analysis methods utilized include conventional assumption testing and multiple linear regression analysis. The results of the study's tests indicate that the simultaneous impact of leverage, firm size, and total asset turnover on stock returns is not observed. It demonstrates, in part, that: (1) total asset turnover is unrelated to stock returns (2) Stock returns are unaffected by a company's size. (3) The return on stocks is unaffected by leverage.